1989
DOI: 10.1007/bf00036962
|View full text |Cite
|
Sign up to set email alerts
|

Common amino acid sequence domains among the LEA proteins of higher plants

Abstract: LEA proteins are late embryogenesis abundant in the seeds of many higher plants and are probably universal in occurrence in plant seeds. LEA mRNAs and proteins can be induced to appear at other stages in the plant's life by desiccation stress and/or treatment with the plant hormone abscisic acid (ABA). A role in protecting plant structures during water loss is likely for these proteins, with ABA functioning in the stress transduction process. Presented here are conserved tracts of amino acid sequence among LEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
529
0
4

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 746 publications
(547 citation statements)
references
References 13 publications
14
529
0
4
Order By: Relevance
“…Four names have been designated for this protein family-RAB, LEA D-11, LEA (II) and DHNs (dehydrins) (Baker et al, 1988;Dure et al, 1989). Dehydrins (dehydration induced) are water deficit-induced genes customarily expressed in the embryos during the late stages of embryogenesis and are also induced in vegetative tissues during normal growth conditions and in response to stress leading to cellular dehydration (e.g.…”
Section: Group 2 Lea Protein/dehydrins (Dhns)mentioning
confidence: 99%
“…Four names have been designated for this protein family-RAB, LEA D-11, LEA (II) and DHNs (dehydrins) (Baker et al, 1988;Dure et al, 1989). Dehydrins (dehydration induced) are water deficit-induced genes customarily expressed in the embryos during the late stages of embryogenesis and are also induced in vegetative tissues during normal growth conditions and in response to stress leading to cellular dehydration (e.g.…”
Section: Group 2 Lea Protein/dehydrins (Dhns)mentioning
confidence: 99%
“…lea genes are ubiquitous in monocots and dicots (Dure et al, 1989). They are characterized by their ABA-modulated expression in late maturation phase embryos and by their ABA-induced expression in response to various environmental stresses, including desiccation (Skriver and Mundy, 1990).…”
Section: Regulation Of Lea Genesmentioning
confidence: 99%
“…The existence in other species of sequence homologs of many of the lea genes became apparent shortly thereafter (collated in Dure et al, 1989), suggesting that they are ubiquitous in the seeds of higher plants. Further, it was found that severa1 of these gene families could be induced to high levels of expression in nonseed organs by ABA andlor water stress (reviewed by Skriver and Mundy, 1990).…”
Section: Introductionmentioning
confidence: 99%